Energy Drinks and Their Impact on the Cardiovascular System: Potential Mechanisms - Grasser, Erik Konrad; Miles-Chan, Jennifer Lynn; Charrière, Nathalie; Loonam, Cathríona R; Dulloo, Abdul G; Montani, Jean-Pierre (Advances in nutrition (Bethesda, Md.), 2016)
Globally, the popularity of energy drinks is steadily increasing. Scientific interest in their effects on cardiovascular and cerebrovascular systems in humans is also expanding and with it comes a growing number of case reports of adverse events associated with energy drinks. The vast majority of studies carried out in the general population report effects on blood pressure and heart rate. However, inconsistencies in the current literature render it difficult to draw firm conclusions with regard to the effects of energy drinks on cardiovascular and cerebrovascular variables. These inconsistencies are due, in part, to differences in methodologies, volume of drink ingested, and duration of postconsumption measurements, as well as subject variables during the test. Recent well-controlled, randomized crossover studies that used continuous beat-to-beat measurements provide evidence that cardiovascular responses to the ingestion of energy drinks are best explained by the actions of caffeine and sugar, with little influence from other ingredients. However, a role for other active constituents, such as taurine and glucuronolactone, cannot be ruled out. This article reviews the potentially adverse hemodynamic effects of energy drinks, particularly on blood pressure and heart rate, and discusses the mechanisms by which their active ingredients may interact to adversely affect the cardiovascular system. Research areas and gaps in the literature are discussed with particular reference to the use of energy drinks among high-risk individuals.